(3eMGSHI GdJcGdja GdUfGYjIs - (3YGeQ YHO Gddg ehSi(B, (3TbQs ((3YeGf(B:s (3OGQ GdHOGjI(B,s, 2009)
(3eMGSHI GdJcGdja h YdGbJgG HGdeMGSHI h GdYdhe GdgfOSjI h CgOGa eMGSHI GdJcGdja , GdGWGQ GdYGe GfXGe GdJcGdja aj GdJfXje GdGOGQj , JHhjH YfGUQ GdJcGdja , JUeje fXGe GdJcGdja h ebheGJg , YdGbI GOGQI Ch bSe GdJcGdja h GdGOGQI GdGNQi , OhQI JSLjd GdehGO GdhGQOI , SjGSGJ GdJSYjQ GdJbOjQj , GdJcGdja ZjQ GdeHGTQI , fXQjGJ JMejd GdJcGdja , GdJcGdja GdGLeGdjI (B((3GdcdjI (B) (3h GdJcGdja GdeHGTQI , fXQjI GdJcGdja GdeJZjQI (B( (3GdMOjI (B) (3, GdJcGdja GdeSJZdI h fXQjI GdJcGdja GdeYjGQjI GdfeWjI , bhGFe GdGYeGd , MSGH GdJTZjd , OhQI eMGSHI GdJcGdja h JcGdja ChGeQ GdJTZjd , JcGdja eQGMd GdJTZjd , GdJGda ef eQGMd GdJTZjd eY hLhO JeGQjf h CSFdI aj fgGjI cd aUd(B.s
(3eQGLY U(B.265s
Keywords: (3GdJcGdja GdUfGYjIs; (3eMGSHI GdJcGdjas